Meningkatkan Motivasi Belajar Siswa Melalui Pemanfaatan Media Audio Visual : Studi Eksperimen Dalam Pembelajaran Tari - Yoyoh Siti Mariyah; Agus Budiman; Heny Rohayani; Winda Dewi Audina (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to see the influence of audio-visual media in dance learning to increase the learning motivation of class VII-A students at SMPN 1 Mangunjaya. The research method used is the pre-experimental method with the design of The One Group Pretest-Posttest. Data collection techniques using observation techniques, literature studies, interviews and documentation studies. The results showed that there was no significant effect of audio-visual media in increasing the motivation of class VII-A students at SMPN 1 Mangunjaya, seen from the analysis results showed that the t value was 0.015˃0.05 and the t value was 2,600˂ t table 2.042, the results of this analysis showed that dance learning with the application of audio-visual media has no effect in increasing student learning motivation, so the hypothesis decision is that it can be concluded that H1 does not have a significant effect on the variable X1 on Y. Accepting H1 or which means there is no significant difference between the pretest and posttest scores. The conclusion is that the audio-visual media applied in dance learning does not have a significant effect on increasing the motivation of class VII-A students at SMPN 1 Mangunjaya